Aplikasi Berbagai Bahan ZPT Alami untuk Meningkatkan Pertumbuhan Bibit Kemiri Sunan (Reutealis trisperma (Blanco) Airy Shaw) - Kurniati, Fitri; Sudartini, Tini; Hidayat, Dikdik (Jurnal AGRO, 2017)
Candlenut cv. Sunan is alternative biofuels plant also as raw of many industrial products. Its hard pulp seed becomes barrier of germination. This condition can be overcome by giving natural plant growth regulators (PGRs), i,e shallot as auxin source, bamboo shoot as gibberellin source, banana bulb and coconut water as sources of cytokinin. The research aim was knowing effect of various PGRs and their combinations to promote germination and growth of seedling candlenut cv Sunan. The research was done from June to October 2016, in experimental design of Randomized Block Design (RBD), consisted of : a0 : control (without PGRs); a1 : shallot (BM); a2 : bamboo shoot (RB); a3: banana bulb (BP); a4 : coconut water (AK); a5 : BM+ RB; a6 : BM + BP; a7 : BM + AK; a8 : RB+ BP; a9 : RB + AK; a10 : BP + AK; a11 : BM + RB + BP + AK, all repeated three times. The result showed that application of natural PGRs had significant effect on germination percentage, plant height on 30 days after planting (dap), 37 dap, 44 dap, and 51 dap, number of leaves 51 dap. Application of BP + AK gave the best effect on germination (97.78%), but no significant different with RB + BP; BM + RB + BP + AK. Application of BP + AK generated highest plant (13.57 cm). The best of the number of leaves was RB + AK (1.45 leaves). Overall application of natural PGRs from banana bulb + coconut water gave the best effect, besides bamboo shoot and shallot have opportunity to be developed.